Access Decisions in a Partly - Digital World: Comparing Digital Piracy and Legal Modes for Film and Music - Robert Veitch (Copenhagen Business School (CBS), 2003)
The emergence of the Internet in the late 20th century and its continued prominence after the year 2000 have created challenges and opportunities for firms and scholars alike. For firms, information technologies (IT) have facilitated access to foreign markets but exposed them to new forms of competition, both commercial and non-commercial, which have undermined their successes. For scholars, the new contexts created by IT have enabled new forms of behaviour not well explained by existing theory. Confronted by these developments, firms attempted to maintain their business models, while scholars applied established theories to explain and predict decisions and behaviour in the new digital landscape. The emergence of widespread digital film and music piracy facilitated by the Internet provides an example of how existing models are often insufficient to explain behaviours enabled by new technologies. Scholars seeking to explain and predict digital piracy have drawn on theories from across the social sciences to inform their investigations into the phenomenon. While these investigations have revealed important insights into the antecedents of digital piracy, the research literature is limited in three key ways. It is theoretically fragmented. It has largely decontextualised digital piracy by not examining how it occurs in relation to legal access. It has underemphasised factors that vary from title-to-title. This project integrates the key streams of piracy research, namely the research informed by social psychology, criminology, business ethics, marketing and economics, and presents a model that addresses the key limitations in the literature. The model was examined over three successive empirical investigations conducted between the autumn of 2010 and the spring of 2012, drawing on samples of university students and consumers in Denmark. The findings from the investigations emphasise the value of an integrated model that contextualises piracy and includes product-title factors. The model explains more variance in access decisions than the models previously offered in the literature. The empirical findings of the research conducted for the project indicate the importance of product-title factors, namely price perceptions, legal availability, and desirability, in addition to access-mode factors such as subjective norms, ethical judgements, and quality risks. The research contributes to the literature on digital piracy in information systems (IS) by emphasising the importance of producttitle factors in individuals' access decisions. Furthermore, it demonstrates the value of using an integrated theoretical model in IS research, when a variety of potential explanations are offered for behaviour.
hdl:10398/8879
Keywords: 650